Penerapan Media Animasi dan Video untuk Mengembangkan Pemahaman Konsep Siswa pada Pembelajaran Biologi Kelas X SMAN 7 Bone - Resmi Resmi; Nurmi Nurmi; Muhammad Ali (SENTRI: Jurnal Riset Ilmiah, 2026)
Education is a process of changing behavior, adding knowledge, and life experiences so that students become more mature. Education in the digital era is advancing rapidly; advances in technology are not limited to adults; elementary school-age children can also benefit from current technological developments. This research aims to demonstrate how to use animation and video media to enhance students' understanding of biological concepts. The research used is quantitative research with the type of Pre-Experimental Design research with the type of One Group Pre-Test and Post-Test Design. The population comprises 5 classes, and sampling is conducted using purposive sampling. The research sample is class X.E1 with a total of 28 students. The data collection techniques used in this study include the provision of pre- and post-test sheets for student concept understanding and documentation. According to the data analysis that has been carried out using SPSS (Statistical Package for the Social Science) for windows version 23 as a data management tool which shows that the normality test on the Shapiro-Wilk results shows that the Pretest (sig) values > (0.05) or (0.010) > (0.05) and Postest (sig) > (0.05) or (0.215) > (0.05) are normally distributed. After the normality test is carried out, a homogeneity test is then carried out to find out whether the data from the population is homogeneous or not, stating the probability (0.042) > (0.05), so that it can be concluded that the homogeneous population is accepted.